Linking Environmental Orientation, Performance, Green Business Strategy: On Mediating Role of Top Management Environmental Awareness Financial Based in SMEs - Adiba Fuad Syamlan; Firdaus Indrajaya Tuharea; Rusdiyanto Rusdiyanto; I Made Landhep Wibawa; Sadine Naomi Safira (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study has a topic regarding the role of top management environmental awareness (TMEA) in mediating the correlation between environmental orientation (EO) and environmental performance (EP) with the adoption of green business strategy (GBS) among small and medium enterprises (SMEs) in Gresik, Indonesia. Using a quantitative approach, there is 151 SMEs data collected then analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that EO and EP do not directly influence GBS. Instead, both significantly affect TMEA, which in turn mediates their impact on GBS. Moreover, SMEs' performance (SP) demonstrates a significant effect on GBS, underscoring the importance of firm performance as a control variable. These findings contribute to the Resource-Based View (RBV) and Dynamic Capabilities theory by positioning managerial awareness as a critical intangible capability that enables firms to translate environmental orientations into strategic actions. Stakeholder Theory is also supported, as external pressures prove effective only when internalized by top managers. The study provides practical implications for SME managers, highlighting the need to enhance managerial environmental awareness through training and leadership development. Limitations include the geographic focus on Gresik and the cross-sectional design, which restricts generalizability and causal inference. Future research should extend to broader contexts and adopt longitudinal methods. Overall, the study advances theoretical and practical understanding of how managerial awareness fosters green strategies in SMEs.